British identities and English Renaissance literature - Baker, David J. (Cambridge University Press, 2002)
Machine generated contents note: I OPENING THE FIELD -- 1 British history and 'The British history': the same old story? -- Philip Schwyzer -- 2 Revising criticism: Ireland and the British model -- Andrew Murphy --II CONTESTED PERIPHERIES -- 3 'The lost British lamb': English Catholic exiles and the problem of Britain -- Christopher Highley -- 4 Making history: Holinshed's Irish Chronicles, 1577 and 1587 -- Richard A. McCabe --III BRITISH SHAKESPEARE -- 5 Henry IV: metatheatrical Britain -- Matthew Greenfield -- 6 Uncertain unions: Welsh leeks in Henry V -- Patricia Parker -- 7 Delving to the root: Cymbeline, Scotland, and the English race -- Mary Floyd- Wilson --IV UNION QUESTIONS -- 8 Reinventing the matter of Britain: undermining the state in Jacobean masques -- Philippa Berry and Jayne Elisabeth Archer -- 9 'Mapping British identities: Speed's Theatre of the Empire of Great Britaine -- Christopher Ivic --V BRITAIN'S BRAVE NEW WORLD -- 10 Bruited abroad:John White and Thomas Harriot's colonial representations of ancient Britain -- Andrew Hadfield -- 11 The commonwealth of the word: New England, Old England, and the praying Indians -- Linda Gregerson --VI RESTORING BRITAIN -- 12 Orrery's Ireland and the British problem, 1641-1679 -- John Kerrigan -- 13 Jacobite literature and national identities -- Murray Pittock -- VII HISTORIANS RESPOND -- 14 Literature and the new British and Irish histories -- Jane Ohlmeyer -- 15 Text, time, and the pursuit of 'British identities' -- Derek Hirst